Helping children left behind : state aid and the pursuit of educational equity - Yinger, John, 1947- (MIT Press, 2004)
Federal reform legislation declares, through its title, that no child should be left behind. Despite this, the sad truth is that many children are being left behind, particularly in large, poor, urban school districts. Because of this inequity, state supreme courts have thrown out the education finance systems in eighteen states, and many states have implemented major education finance reforms. These reforms have lessened disparities in educational spending but appear to have had little impact on disparities in educational performance. Helping Children Left Behind explores both the general issues in education finance reform and the experiences of five states to understand why these disparities persist and to design policies that address them. The book is a valuable resource for scholars, public officials, and others interested in education finance reform. The first part of the book addresses the general issues involved in reform of state aid to education. After a comprehensive introductory chapter that outlines such issues as selecting aid formulas, adjusting for disadvantaged students, district accountability, and school choice, the chapters in part I examine these issues in more depth, discussing court cases involving school finance reform, the relationship between funding and accountability, and the consequences and feedback effects of school aid reform policies, including the effect on residential patterns. The second part of the book consists of detailed case studies of recent ambitious school finance reform efforts in Kansas, Kentucky, Michigan, Texas, and Vermont. Three appendixes offer valuable reference material, describing significant state court decisions on school finance systems (through June 2003), state operating aid programs, and state building aid formulas.